2007
DOI: 10.1136/jnnp.2007.121525
|View full text |Cite
|
Sign up to set email alerts
|

Case control study of diffusion tensor imaging in Parkinson's disease

Abstract: We demonstrated in a large, prospective, case control study that the FA value in the substantia nigra on DTI was lower in PD compared with healthy controls, and correlated inversely with the clinical severity of PD. Further longitudinal studies would be helpful to assess the clinical utility of serial FA measurements of the substantia nigra in objective quantification of disease progression and monitoring of the therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
160
6
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(190 citation statements)
references
References 21 publications
20
160
6
4
Order By: Relevance
“…The current study extends the previous literature to show that early stage, de novo patients with PD have reduced FA in the SN. In addition, although group-level differences for FA in the SN were significant in both previous studies between patients with PD and control subjects, 4,6 on an individual basis, FA measures could not identify PD patients consistently. For instance, a case-controlled study 4 reported an area under the curve that was considered modest (0.653), suggesting that DTI may not be a promising method for identifying PD in individual subjects.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The current study extends the previous literature to show that early stage, de novo patients with PD have reduced FA in the SN. In addition, although group-level differences for FA in the SN were significant in both previous studies between patients with PD and control subjects, 4,6 on an individual basis, FA measures could not identify PD patients consistently. For instance, a case-controlled study 4 reported an area under the curve that was considered modest (0.653), suggesting that DTI may not be a promising method for identifying PD in individual subjects.…”
Section: Resultsmentioning
confidence: 57%
“…4,6 In those studies, patients were more severely impaired than the patients in the current study, and the patients in these two previous studies were examined while on dopaminergic medication. The current study extends the previous literature to show that early stage, de novo patients with PD have reduced FA in the SN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study, along with another, 24 did not find an association between disease severity and FA in SN. Two other studies 10,26 did find reduced FA in SN correlated with disease severity. Studies focusing on the SN and integrating T2* 20,24 or volumetric analysis 15 with DTI reported that this improved their ability to discriminate patients with PD from healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…The most common finding in many DTI studies was a reduction in fractional anisotropy (FA) in the substantia nigra of PD patients (Chan et al, 2007;Du et al, 2011;Peran et al, 2010;Vaillancourt et al, 2009;Yoshikawa, Nakata, Yamada, & Nakagawa, 2004), and the reduction in FA values in the substantia nigra was inversely correlated with the severity of the clinical symptoms of PD patient (Chan et al, 2007). Extranigral WM changes have been observed in PD patients.…”
Section: Structural Connectivitymentioning
confidence: 99%